Complications after different surgical methods of setting polypropylene suburethral meshes in women with stress urinary incontinence - Eisenakh I.A.; Korotkevich O.S.; Mozes V.G.; Vlasova V.V. (Саратовский научно-медицинский журнал, 2018)
The aim: to determine the complication's rate, based on a seven-year experience, after the stress urinary incontinence correction in women with different methods of setting suburethral polypropylene meshes. Material and Methods. The analysis of seven years of experience of surgical correction with different methods of setting suburethral meshes in 1260 women with stress urinary incontinence; obturator fixation the mesh inside-outside and outside-inside: supra-pubic fixation the mesh; non-trocar fixation the mesh type mini-sling was carried out. Results. The greatest frequency of complications were identified in the first two years of implementation the setting of suburethral meshes, after that the complication's rate decreased progressively and it was in the range 7-8% the last three years. The frequency of early operative complications at a different setting of suburethral meshes had no statistically significant differences, but there were more the statistically significant intraoperative and mesh-associated complications at suprapubic fixation. Conclusion. The study confirms that the installation of suburethral meshes by the method of suprapubic fixation of mesh is associated with a higher incidence of complications and should be performed only in the target group of patients who are not suitable for surgical correction in safer ways.